Highly Efficient Electrocatalysts for Oxygen Reduction Based on 2D Covalent Organic Polymers Complexed with Non-precious Metals - Xiang, Zhonghua; Xue, Yuhua; Cao, Dapeng; Huang, Ling; Chen, Jian-Feng; Dai, Liming (Angewandte Chemie International Edition, 2014)
A class of 2D covalent organic polymers (COPs) incorporating a metal (such as Fe, Co, Mn) with precisely controlled locations of nitrogen heteroatoms and holes were synthesized from various N‐containing metal–organic complexes (for example, metal–porphyrin complexes) by a nickel‐catalyzed Yamamoto reaction. Subsequent carbonization of the metal‐incorporated COPs led to the formation of COP‐derived graphene analogues, which acted as efficient electrocatalysts for oxygen reduction in both alkaline and acid media with a good stability and free from any methanol‐crossover/CO‐poisoning effects. Metal‐containing (M=Fe, Co, Mn) 2D covalent organic polymers with precisely controlled locations of N heteroatoms and holes were synthesized from metal–porphyrin complexes by a nickel‐catalyzed Yamamoto reaction. Subsequent carbonization led to graphene analogues, which are efficient electrocatalysts for oxygen reduction in both alkaline and acid media and are free from methanol‐crossover/CO poisoning.